CESIUM CHEMISORPTION ONTO STAINLESS STEEL UNDER SIMULATED LIGHT WATER REACTOR SEVERE ACCIDENT - Ngarayana, I Wayan (Website, 2023)
During light water reactor severe accident, source terms may interact with structural materials, generating new compounds and affecting their volatility which make the existing codes could not accurately estimate the radioactive release. Cesium is one of the source terms that can interact with structural materials and contributes greatly to the late release phenomenon. Several studies have been conducted to predict the physicochemical interactions between cesium and structural materials. However, the types of chemisorbed cesium compounds onto structural materials are still under discussion. For this reason, this study was carried out using advanced techniques, involving TEM, SEM, EDS and FIB to estimate the chemisorbed cesium compounds onto stainless steel structural material under simulated light water severe accident. This study indicates that cesium is strongly adsorbed on the oxide layer of stainless steel in the form of cesium silica, cesium aluminum silica, and/or cesium ferro silica. CsFeSiO4 and CsAlSiO4 could dominate these compounds.